1991
DOI: 10.1002/prot.340090204
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bonds involving sulfur atoms in proteins

Abstract: Intrachain hydrogen bonds are a hallmark of globular proteins. Traditionally, these involve oxygen and nitrogen atoms. The electronic structure of sulfur is compatible with hydrogen bond formation as well. We surveyed a set of 85 high-resolution protein structures in order to evaluate the prevalence and geometry of sulfur-containing hydrogen bonds. This information should be of interest to experimentalists and theoreticians interested in protein structure and protein engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
204
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 239 publications
(225 citation statements)
references
References 19 publications
21
204
0
Order By: Relevance
“…Although sulfur is not as electronegative as oxygen, it would still be expected to make an excellent nucleophile for attack on the acetyl carbonyl carbon. The slightly longer sulfur-carbon bond pushes the sulfur atom into a position such that it can make potential hydrogen bonds with both His 158 and His 193 that are significantly longer than the corresponding oxygen hydrogen bonds (32 His 158 and the O␥ of serine would prevent the formation of a hydrogen bond to His 193 at the same time, thus the binding of cysteine is expected to be significantly tighter than that of serine, and this may increase the activation energy sufficiently to prevent catalysis. This difference in binding may account for some of the 4.4 kcal⅐mol Ϫ1 apparent difference in binding energies of serine and cysteine calculated by Hindson (16).…”
Section: Discussionmentioning
confidence: 99%
“…Although sulfur is not as electronegative as oxygen, it would still be expected to make an excellent nucleophile for attack on the acetyl carbonyl carbon. The slightly longer sulfur-carbon bond pushes the sulfur atom into a position such that it can make potential hydrogen bonds with both His 158 and His 193 that are significantly longer than the corresponding oxygen hydrogen bonds (32 His 158 and the O␥ of serine would prevent the formation of a hydrogen bond to His 193 at the same time, thus the binding of cysteine is expected to be significantly tighter than that of serine, and this may increase the activation energy sufficiently to prevent catalysis. This difference in binding may account for some of the 4.4 kcal⅐mol Ϫ1 apparent difference in binding energies of serine and cysteine calculated by Hindson (16).…”
Section: Discussionmentioning
confidence: 99%
“…Cohen and coworkers have surveyed the protein data bank and found that 72% of all reduced cysteine residues in proteins are involved in hydrogen bonding (Gregoret et al, 1991). Of these residues, 58% are involved in hydrogen bonding to carbonyl oxygens at position i-4 of an ␣-helix.…”
Section: Sulfhydryl Vibrational Modes: Hydrogen-bonding and Conformationmentioning
confidence: 99%
“…Ecotin's secondary binding site for proteases buries little surface area and would probably be unstable in the absence of the primary interaction. (Gellman, 1991) as well as being a potential hyfound between ecotin Met 84-N (Pl) and trypsin Ser 214-0, and drogen bond acceptor (Gregoret et al, 1991). between ecotin Ser 82-N and 0 (P3) with trypsin Gly 216-0 and N, respectively.…”
Section: Figmentioning
confidence: 99%